Combining parenting and economic strengthening programmes to reduce violence against children: a cluster randomised controlled trial with predominantly male caregivers in rural Tanzania. Issue 7 (8th July 2020) - Lachman, Jamie; Wamoyi, Joyce; Spreckelsen, Thees; Wight, Daniel; Maganga, Jane; Gardner, Frances
Abstract : Introduction: Parenting programmes may reduce the risk of violence against children and improve child well-being. However, additional economic support may be necessary in highly deprived rural communities in sub-Saharan Africa. Furthermore, delivering programmes within farmer groups may increase male caregiver recruitment and engagement. Methods: A parallel cluster randomised controlled trial examined the combined and separate effects of parenting and economic strengthening programmes on reducing violence against children aged 0–18 years in farming communities in Tanzania (n=248 families; 63% male caregivers). Eight villages were randomly assigned to four conditions (2:2:2:2): (1) 12-session parenting programme (n=60); (2) agribusiness training (n=56); (3) parenting and agribusiness combined (n=72); (4) control (n=60). Parent-report, child-report and early childhood observation assessments were conducted at baseline, mid-treatment and post-treatment. Primary outcomes were child maltreatment and parenting behaviour. Secondary outcomes included corporal punishment endorsement, parenting stress, parent/child depression, child behaviour, economic well-being and child development. Results: At post-treatment, parents and children receiving the combined interventions reported less maltreatment (parents: incidence rate ratio (IRR=0.40, 95% CI 0.24 to 0.65; children: IRR=0.40, 95% CI 0.17 to 0.92). Parents reported reduced endorsement of corporal punishment ( Dw =−0.43, 95% CI −0.79 to 0.07) and fewer child behaviour problems ( Dw =−0.41, 95% CI −0.77 to 0.05). Parents in parenting-only villages reported less abuse (IRR=0.36, 95% CI 0.21 to 0.63) and fewer child behaviour problems ( Dw =−0.47, 95% CI −0.84 to 0.11). Parents in agribusiness-only villages reported fewer child behaviour problems ( Dw =−0.43, 95% CI −0.77 to 0.08) and greater household wealth ( Dw =0.57, 95% CI 0.08 to 1.06). However, children in agribusiness-only villages reported increased physical abuse (IRR=2.26, 95% CI 1.00 to 5.12) and less positive parenting ( Dw =−0.50, 95% CI −0.91 to 0.10). There were no other adverse effects. Conclusion: Parent training may be the active ingredient in reducing maltreatment in farmer groups with majority male caregivers, while agribusiness training programmes may have unintended negative consequences on children when delivered alone. Locating parenting support in existing farmer groups can engage much higher proportions of fathers than stand-alone programmes. ClinicalTrials.gov: NCT02633319